Differential effects of threat types on attentional processes: a comparison of snakes and blood-injury-injection stimuli - Zsido, Andras Norbert; Kiss, Botond László (Frontiers in Psychiatry, 2024)
IntroductionPrevious research on the visual processing of threats has largely overlooked the Q8 distinct effects of various types of threats, despite evidence suggesting unique brain activation patterns for specific fears. Our study examines the differential effects of threat types on attentional processes, focusing on snakes and blood-injury-injection (BII) stimuli. We sought to test whether these two types of threat stimuli, as taskirrelevant distractors, would lead to similar effects in a visual search task.MethodsParticipants were exposed to emotionally charged stimuli of varying arousal (medium and high) and neutral pictures of low arousal as task-irrelevant distractors while performing a primary visual search task.ResultsWe found that BII-related distractor pictures interfered with attention to the primary task, resulting in slower reaction times compared to snake pictures. In addition, BII-related medium arousal stimuli decreased, but high arousal facilitated both orienting and executive attentional performance. Exploratory analysis of personality traits revealed differential effects of trait anxiety and disgust sensitivity, highlighting the unique mechanisms underlying fear responses. In addition, participants who used adaptive emotion regulation strategies showed better performance in overcoming the interference of threat stimuli on attention.DiscussionThese findings underscore the importance of considering individual differences and emotion regulation strategies in fear research and provide insight into the complex interplay between threat perception and attentional processes.